Performance Enhancement of R.C. Beams with Large Web Openings by Using Reactive Powder Composite: An Experimental Study - Jassim, Nidaa Qassim; Jarallah, Husain Khalaf (Al-Nahrain Journal for Engineering Sciences, 2018)
In this paper an experimental works conducted to study the behavior of R.C. beam with large web opening at different locations and fortified with reactive powder composite (RPC) at the extreme tension zone (bottom edge of opening) and/or extreme compression zone (Top edge of opening). The experimental study is investigate the behavior of twelve beams and study the ability of using normal strength concrete together with RPC in the same section to exploit the advantages of these two materials in optimal way. The main variables are RPC layers locations in tension zone and/or in compression zone and the locations of openings. The ultimate loads, load mid-span deflection behavior and strain for steel and concrete were discussed. The experimental results showed that the ultimate strength was decreased with increasing number of opening about 4% for beams with two openings located in shear zone and 21% for beams with three openings, thus indicating that the stiffness decreases accordingly. The using RPC layers effectively enhanced performance of hybrid beams when compared with using the normal strength concrete layers only. The using RPC layers in compression and tension zones increased the ultimate load about 47 % for beams with two opening located in shear zone, when using RPC in the tension zone and normal strength concrete in the compression zone the ultimate flexural load and ultimate deflection increase little compared with normal concrete.